PERSEPSI MAHASISWA BARU FAKULTAS KEDOKTERAN UNIVERSITAS PATTIMURA TERHADAP PELAKSANAAN TUTORIAL PROBLEM BASED LEARNING (PBL) - Hetharia, Leoni Miraty; Tentua, Vebiyanti; Noiza, Stazia (PAMERI, 2024)
Background: Tutorial Problem Based Learning (PBL) is a form of group discussion that aims to form a collaborative, contextual and constructive learning process. This method is a learning method that has just been adopted by new students at the Faculty of Medicine, Patimura University, from conventional learning methods to student-centered learning methods. Based on the results of initial interviews with new students, it was found that there were various views from students regarding the implementation of PBL tutorials. Aims: This study aims to find out more about student perceptions regarding the implementation of PBL tutorials. Methods: This research is a qualitative research method with a phenomenological approach and data collection techniques using in-depth interviews and FGD (Focus Group Discussion). Result: The results of this study indicate that PBL tutorials can help students in the collaboration process and think contextually and constructively. Regarding the scenarios in this study, students said they were more stimulated to learn with the new scenarios given compared to the old scenarios, for the role of tutors there are several tutors who need to pay attention to their role in evaluating and assessing during the PBL tutorial process and for students in the PBL tutorial process in this study it is stated students can be active in discussions, but are influenced by prior knowledge of students, the number of group members and self-confidence. Conclusion: Therefore, to increase the effectiveness of PBL tutorials implemented at the Faculty of Medicine, University of Pattimura, it is necessary to update the scenarios given, evaluate tutors regarding the role and assessment in the PBL tutorial process and increase student understanding regarding the objectives of implementing PBL tutorials.